Construction method and application of photoexcitation type nitrogen oxide sensor
Patent Information
- Application Number
- CN202611290437.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-23
AI Technical Summary
但是在缺乏外部热激发的环境中,当气体接触敏感材料表面并吸附后,由于脱附活化能较高,使得传感器在室温下响应后基线漂移严重、无法自发恢复,即出现表面“中毒”现象
本发明整个二硫化锡纳米颗粒状和硫化铋纳米棒状气敏材料的制备方法简单,易于操作,且基于所得二硫化锡纳米颗粒状和硫化铋纳米棒状气敏材料构筑的传感器对氮氧化物气体表现出极低检测下限、高灵敏、高稳定性、高选择性等优异的传感特性;
Smart Images

Figure CN122962064A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nitrogen oxide gas sensor technology, specifically a method for constructing and applying a photoexcited nitrogen oxide sensor. Background Technology
[0002] Inorganic trace gases in human exhaled breath are important biomarkers reflecting changes in the body's basal metabolism and pathological microenvironment. Detection of these gases is of significant practical importance for the early diagnosis of diseases. Nitric oxide (NO) and its derivatives (NO2) play a role in immune defense and airway inflammation regulation in the human respiratory system. In the pathogenesis of chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD), the levels of nitrogen oxides (NO2) in the patient's exhaled breath are high. x The concentration of exhaled NO tends to increase, typically exceeding 50 ppb. In contrast, the concentration of exhaled NO in healthy individuals is extremely low, usually below 25 ppb. Exhaled breath detection technology exhibits significant non-invasiveness, immediate response capability, and dynamic tracking potential; therefore, a miniaturized, low-detection-line, high-response, and safe NO detection method is needed. x Gas sensors are used to assess the level of local inflammation in a patient's airway, providing an important pathway for health assessment and early disease diagnosis.
[0003] Compared to traditional metal oxides, low-dimensional metal sulfides, such as tin disulfide (SnS2) and bismuth sulfide (Bi2S3), have gradually attracted attention. These sulfide semiconductors possess layered structures, large specific surface areas, and narrow intrinsic band gaps. However, in environments lacking external thermal excitation, when gases come into contact with and adsorb onto the surface of the sensitive material, the high desorption activation energy causes severe baseline drift after the sensor responds at room temperature, preventing spontaneous recovery—a phenomenon known as surface "poisoning." To address the difficulty of desorption of metal sulfides at room temperature, a multi-band photoexcitation strategy can be introduced to improve the gas-sensing response time of gas sensors and accelerate their recovery speed.
[0004] Therefore, the nitrogen oxide gas sensor based on tin disulfide nanoparticles and bismuth sulfide nanorods that we proposed has a wide range of applications and provides important technical support for the early non-invasive diagnosis of health status and diseases. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, at least one technical problem raised in the background art is solved.
[0006] The technical solution adopted by this invention to solve its technical problem is: a method for constructing a photoexcited oxynitride sensor, comprising the following steps: S1. Add tin tetrachloride pentahydrate and bismuth chloride to thiourea, dissolve them in deionized water, stir evenly, and carry out hydrothermal reaction to obtain tin disulfide nanoparticles and bismuth sulfide nanorods, respectively. S2. Tin disulfide nanoparticles and bismuth sulfide nanorods are added to a mixed solution of naphthol and terpineol, respectively, and then screen-printed onto the surface of interdigitated electrodes to construct a nitrogen oxide gas sensor.
[0007] Preferably, in S1, the ratio of tin tetrachloride pentahydrate, thiourea, and deionized water is 175.31 mg: 76.12 mg: 35 mL.
[0008] Preferably, in S1, the ratio of bismuth chloride, thiourea, and deionized water is 630.68 mg: 304.48 mg: 70 mL.
[0009] Preferably, in S1, the hydrothermal reaction time is 7.5 h.
[0010] Preferably, the morphology of the tin disulfide nanoparticle composite gas-sensitive material is a loose and rough stacked particle structure.
[0011] Preferably, the bismuth sulfide nanorods exhibit a large number of rod-shaped and columnar crystal bundles.
[0012] Preferably, in S2, the mass ratio of tin disulfide nanoparticles to bismuth sulfide nanorod gas-sensitive material is 25 mg: 25 mg.
[0013] Preferably, in S2, the volume ratio of naphthol to terpineol is 2 μL: 12 μL.
[0014] Preferably, the size of the interdigital electrode is 5.5 mm × 5.5 mm, the size of the sensitive area is 2.2 mm × 2.2 mm, the interdigital spacing is 0.2 mm, and a 1 mm diameter perforation is designed at each of the four corners of each independent electrode.
[0015] An application of a photoexcited nitrogen oxide sensor: Tin disulfide nanoparticles and bismuth sulfide nanorods prepared by the above method are added to 2 μL of naphthol and 12 μL of terpineol, respectively, and then ground in a quartz mortar. Subsequently, they are screen-printed onto the surface of interdigital electrodes and allowed to dry completely to form a gas sensor, which is then used for nitrogen oxide gas sensing.
[0016] The beneficial effects of this invention are as follows: The preparation method of the entire tin disulfide nanoparticle and bismuth sulfide nanorod gas-sensitive materials of the present invention is simple and easy to operate. Moreover, the sensor constructed based on the obtained tin disulfide nanoparticle and bismuth sulfide nanorod gas-sensitive materials exhibits excellent sensing characteristics such as extremely low detection limit, high sensitivity, high stability and high selectivity for nitrogen oxide gas. In the process of constructing a nitrogen oxide gas sensor using tin disulfide nanoparticles and bismuth sulfide nanorods, the present invention describes how the prepared tin disulfide nanoparticles and bismuth sulfide nanorods are processed through a sensor sensitive thin film process to construct a nitrogen oxide gas sensor, which can achieve rapid sensing response to nitrogen oxide gas and exhibit excellent gas sensing characteristics. Attached Figure Description
[0017] The invention will now be further described with reference to the accompanying drawings.
[0018] Figure 1 These are SEM images of the tin disulfide nanoparticles and bismuth sulfide nanorods gas-sensitive material samples prepared in this invention. Figure 1 Image a is a SEM image of tin disulfide nanoparticles. Figure 1 Image b in the image is a SEM image of bismuth sulfide nanorod-shaped gas-sensitive material. Figure 2 These are schematic diagrams of the self-made interdigitated electrode circuit design of this invention and actual images of the mass-produced printed circuit. Figure 2 In the diagram, 'a' represents the design schematic of the interdigital electrode circuit. Figure 2 Image b in the middle is a picture of the actual product after mass printing; Figure 3 These are XRD images of the tin disulfide nanoparticles and bismuth sulfide nanorods gas-sensitive materials provided by this invention. Figure 4 The table shows the Response (Rair / Rgas)-Time (s) curves of the gas-sensing performance of the tin disulfide nanoparticles and bismuth sulfide nanorods prepared in this invention to nitrogen oxide gases under different photoexcitation conditions. Figure 4 In Figure 'a', the response (Rair / Rgas)-Time(s) curves of tin disulfide nanoparticles under different photoexcitation conditions are shown. Figure 4 In the middle b, the response (Rair / Rgas)-Time (s) curves of the bismuth sulfide nanorod gas-sensing material to nitrogen oxide gas under different photoexcitation conditions are shown. Figure 5 Bar graphs showing the gas-sensing response values of the tin disulfide nanoparticles and bismuth sulfide nanorods prepared in this invention to seven gases (hydrogen, methane, ammonia, trimethylamine, sulfur dioxide, nitric oxide, and nitrogen dioxide) under different light conditions. Detailed Implementation
[0019] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.
[0020] Example 1 The method for constructing a photoexcited oxynitride sensor according to an embodiment of the present invention includes the following steps: Step 1: Weigh 175.31 mg of tin tetrachloride pentahydrate and 76.12 mg of thiourea, dissolve them in 35 mL of deionized water, and stir evenly for 30 min to obtain a transparent solution of the first precursor; transfer the transparent solution of the first precursor to a 50 mL polytetrafluoroethylene liner, seal the liner and place it in a reaction vessel, and place the reaction vessel in an oven for hydrothermal reaction at 210 ℃ for 7.5 h; to obtain tin disulfide nanoparticles; 630.68 mg of bismuth chloride and 304.48 mg of thiourea were weighed and dissolved in 70 mL of deionized water. The mixture was stirred evenly for 30 min to obtain a transparent solution of the second precursor. The transparent solution of the second precursor was transferred to a 50 mL polytetrafluoroethylene liner. The liner was sealed and placed in a reaction vessel. The reaction vessel was placed in an oven for hydrothermal reaction at 210 °C for 7.5 h to obtain bismuth sulfide nanorod gas-sensitive materials. After the hydrothermal reaction is completed, the reactor is allowed to cool naturally to room temperature. The reactor is then opened and the liner is removed. The suspension in the liner is transferred to a 50 mL centrifuge tube. The precipitate in the liner is washed and centrifuged with deionized water and anhydrous ethanol. The collected precipitate is then dried. The sediment in the lining was centrifuged three times at a speed of 8000 rpm for 5 min; the drying temperature was 60 ℃ and the drying time was 6 h. Step 2: Add 25 mg of tin disulfide nanoparticles and 25 mg of bismuth sulfide nanorod gas-sensitive material to a mixed solution of 2 μL naphthol and 12 μL terpineol, respectively, and then screen print them onto the surface of the interdigitated electrode. Dry the electrode in an oven at 80 °C for 30 min to construct a semiconductor sensor that can be used to detect nitrogen oxide gas.
[0021] The preparation process of the tin disulfide nanoparticles and bismuth sulfide nanorods gas-sensitive materials is simple and easy. The sensors constructed based on the obtained tin disulfide nanoparticles and bismuth sulfide nanorods gas-sensitive materials exhibit sensing performance such as low detection limit, high sensitivity, high stability and high selectivity for the detection of nitrogen oxides.
[0022] Example 2 This invention provides an application of a photoexcited room-temperature nitrogen oxide gas sensor. The tin disulfide nanoparticles and bismuth sulfide nanorods prepared in the above embodiments can be used for the rapid detection of nitrogen oxide gases. Specifically: The interdigitated electrodes measure 5.5 mm × 5.5 mm, with a sensitive area measuring 2.2 mm × 2.2 mm and an interdigital spacing of 0.2 mm. Each individual electrode has 1 mm diameter perforations at its four corners. Gold deposition was applied to the two ends of the sensing end to optimize the conductivity between the sensing end and the chip socket pins. Conversely, the two lower holes were intentionally left uncovered with gold to prevent the sensitive material from diffusing into the pins and affecting sensing performance.
[0023] 25 mg of tin disulfide nanoparticles and 25 mg of bismuth sulfide nanorods were added to 2 μL of naphthol and 12 μL of terpineol, respectively, and then screen-printed onto the surface of interdigitated electrodes. The electrodes were then dried in an oven at 80 °C for 30 min to construct a semiconductor sensor that can be used to detect nitrogen oxide gas. When tin disulfide nanoparticles and bismuth sulfide nanorods are used in the production process of nitrogen oxide gas sensors, the tin disulfide nanoparticles and bismuth sulfide nanorods prepared in the above embodiments are used to construct nitrogen oxide gas sensors through sensor sensitive film technology. This enables rapid sensing response to nitrogen oxide gas and quickly exhibits excellent gas sensing characteristics.
[0024] Performance testing During the morphology observation and performance testing of the tin disulfide nanoparticles and bismuth sulfide nanorods prepared in the above embodiments, the following results were obtained: like Figure 1 As shown, from Figure 1 The synthesized tin disulfide nanoparticles and bismuth sulfide nanorods are visible. SEM characterization reveals that the tin disulfide nanoparticle composite gas sensor exhibits a loose and coarse stacked morphology, while the bismuth sulfide nanorods show numerous rod-shaped and columnar crystal bundles. This structure provides both the tin disulfide nanoparticles and bismuth sulfide nanorods with a large specific surface area, increasing gas adsorption and lowering the desorption barrier. Upon photoexcitation, the metal sulfides generate electron-hole pairs, enhancing photocatalytic activity, accelerating gas response, and improving recovery efficiency. Under light conditions, the dynamic balance between adsorption and desorption minimizes surface degradation, thus extending the sensor's lifespan.
[0025] like Figure 2As shown, the self-made interdigitated electrodes are 5.5 mm × 5.5 mm in size, the sensitive area is 2.2 mm × 2.2 mm, and the interdigital spacing is 0.2 mm. Each individual electrode has 1 mm diameter through holes at its four corners to facilitate subsequent soldering to the tubular base. Gold deposition was applied to the two ends of the sensing end to optimize the conductivity between the sensing end and the chip-type tube base pins. Conversely, the two holes at the lower end were intentionally left uncovered with gold to prevent the sensitive material from diffusing into the pins and affecting sensing performance.
[0026] like Figure 3 As shown, it is evident that there are obvious diffraction peaks at 15.5°, 32.2°, 41.99°, 50.10°, 52.62°, and 55.14° at the 2θ angle, corresponding to the (001), (011), (012), (110), (111), and (103) crystal planes of tin disulfide, respectively. The XRD diffraction pattern matches well with the standard card (PDF#83-1705), confirming the presence of tin disulfide in the composite sample. There are also obvious diffraction peaks at 22.38°, 24.92°, 25.00°, 25.21°, 28.64°, 31.81°, and 39.91°, corresponding to the (022), (013), (111), (031), (121), and (122) crystal planes of tin disulfide, respectively. Furthermore, no additional diffraction peaks were observed in the sample, indicating that the sample has high crystallinity and no impurity peaks. The above-mentioned gas-sensitive application of tin disulfide nanomaterials of the present invention involves adding 25 mg of tin disulfide material to 2 μL of naphthol and 12 μL of terpineol, respectively, and further screen printing it onto the surface of interdigitated electrodes. After drying in an oven at 80 °C for 30 min, a gas sensor is further constructed, and then gas-sensitive detection is performed. The sensor performs gas-sensitive testing on nitrogen oxide gas under green, blue, purple, and white light. like Figure 4The figure shows the dynamic response curves of the sensor based on tin disulfide nanoparticles and bismuth sulfide nanorods to different concentrations (10 to 500 ppb) of hydrogen sulfide gas at 30% humidity and room temperature. The figure shows that under green, blue, purple, and white light, the response values of tin disulfide to NO are 7.6, 2.6, 2.2, and 2.4, respectively, while those of bismuth sulfide are 1.7, 1.5, 1.6, and 1.2, respectively. The response values of tin disulfide to NO2 are 7.4, 2.2, 1.7, and 2.6, respectively, while those of bismuth sulfide are 1.8, 1.6, 1.5, and 1.3, respectively, highlighting excellent sensing performance. Furthermore, the sensitivity of this gas sensor increases with increasing nitrogen oxide gas concentration, indicating that the prepared sensor has good reversibility. like Figure 5 The figure shows a bar graph illustrating the response values of sensors based on tin disulfide nanoparticles and bismuth sulfide nanorods to seven gases at a concentration of 10 ppm (hydrogen, methane, ammonia, trimethylamine, sulfur dioxide, nitric oxide, and nitrogen dioxide) at a humidity of 30% and room temperature. The graph shows that the sensors based on tin disulfide nanoparticles and bismuth sulfide nanorods exhibit good responses to the aforementioned nitrogen oxide gases.
[0027] In summary, the tin disulfide nanoparticles and bismuth sulfide nanorods of the present invention exhibit excellent gas-sensing properties at room temperature.
[0028] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for constructing a photoexcited oxide nitride sensor, characterized in that: Includes the following steps: S1. Add tin tetrachloride pentahydrate and bismuth chloride to thiourea, dissolve them in deionized water, stir evenly, and carry out hydrothermal reaction to obtain tin disulfide nanoparticles and bismuth sulfide nanorods, respectively. S2. Tin disulfide nanoparticles and bismuth sulfide nanorod gas-sensitive materials are respectively added to a mixed solution of naphthol and terpineol, and then screen-printed onto the surface of interdigitated electrodes to construct a nitrogen oxide gas sensor. In S1, the ratio of tin tetrachloride pentahydrate, thiourea, and deionized water was 175.31 mg: 76.12 mg: 35 mL; In S1, the ratio of bismuth chloride, thiourea, and deionized water was 630.68 mg: 304.48 mg: 70 mL. The morphology of the tin disulfide nanoparticle composite gas-sensitive material is a loose and coarse stacked particle structure. Bismuth sulfide nanorods exhibit numerous rod-shaped and columnar crystal bundles; In S2, the mass ratio of tin disulfide nanoparticles to bismuth sulfide nanorod gas-sensitive materials is 25 mg: 25 mg.
2. The method for constructing a photoexcited oxynitride sensor according to claim 1, characterized in that: In S1, the hydrothermal reaction time is 7.5 h.
3. The method for constructing a photoexcited oxynitride sensor according to claim 2, characterized in that: In S2, the volume ratio of naphthol to terpineol is 2 μL: 12 μL.
4. The method for constructing a photoexcited oxynitride sensor according to claim 3, characterized in that: The interdigitated electrode measures 5.5 mm × 5.5 mm, the sensitive area measures 2.2 mm × 2.2 mm, the interdigital spacing is 0.2 mm, and each individual electrode has a 1 mm diameter perforation at each of its four corners.
5. An application of a photoexcited nitrogen oxide sensor, characterized in that, The tin disulfide nanoparticles and bismuth sulfide nanorods gas-sensitive materials prepared by the method according to any one of claims 1-4 are respectively added to 2 μL of naphthol and 12 μL of terpineol, then ground in a quartz mortar, and subsequently printed on the surface of interdigitated electrodes by screen printing plate. After being completely dried, they are used to form a gas sensor and further used for nitrogen oxide gas sensing detection.